2019
DOI: 10.1101/19002998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of Serum Neurofilaments as Prognostic & Potential Pharmacodynamic Biomarkers for ALS

Abstract: Objective. Identify preferred neurofilament assays, and clinically validate serum NfL and pNfH as prognostic and potential pharmacodynamic biomarkers relevant to ALS therapy development. Methods. Prospective, multi-center, longitudinal observational study of patients with ALS (n=229), primary lateral sclerosis (PLS, n=20) and progressive muscular atrophy (PMA, n=11). Biological specimens were collected, processed and stored according to strict standard operating procedures (SOPs) 1. Neurofilament assays were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
(15 reference statements)
7
14
0
Order By: Relevance
“…243 of the 248 SIMOA samples were technically successful. A Cox proportional hazard analysis revealed that high plasma NfL predicts higher risk of death (from enrollment HR 2.09, 95% 1.49 – 2.94, p<0.001, C-index 0.59, Akaike’s information criteria (AIC) 2083, or from onset HR 2.26, 95% 1.73 – 2.96, p<0.001, C-index 0.62, AIC 2060 Figure 5A, B), as previously reported 2830 . The performance of miR-181 in predicting risk of death is comparable with that of NfL (from enrollment HR 2.03, 95% CI: 1.45 – 2.85, p<0.001, C-index 0.56, AIC 2096, or from onset HR 2.07, 95% CI: 1.6 – 2.7, p<0.001, C-index 0.56, AIC 2081, Figure 5A, B).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…243 of the 248 SIMOA samples were technically successful. A Cox proportional hazard analysis revealed that high plasma NfL predicts higher risk of death (from enrollment HR 2.09, 95% 1.49 – 2.94, p<0.001, C-index 0.59, Akaike’s information criteria (AIC) 2083, or from onset HR 2.26, 95% 1.73 – 2.96, p<0.001, C-index 0.62, AIC 2060 Figure 5A, B), as previously reported 2830 . The performance of miR-181 in predicting risk of death is comparable with that of NfL (from enrollment HR 2.03, 95% CI: 1.45 – 2.85, p<0.001, C-index 0.56, AIC 2096, or from onset HR 2.07, 95% CI: 1.6 – 2.7, p<0.001, C-index 0.56, AIC 2081, Figure 5A, B).…”
Section: Resultssupporting
confidence: 85%
“…In such cases, the value of miR-181 may be even more pronounced. In addition, real-world patient profiles indicate that most ALS patients are in the middle tertile neurofilament level, 30 the enhanced sensitivity provided by miR-181 at this region of the spectrum will be particularly useful. Taken together, miR-181 emerges as a prognostic ALS biomarker that can be developed in combination with NfL to improve the accuracy of patient stratification in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…243 of the 248 SIMOA samples were technically successful. A Cox proportional hazard analysis revealed that high plasma NfL predicts higher risk of death (from enrollment HR 2.09, 95% 1.49 -2.94, p<0.001, concordance index (C-index) 0.59, Akaike's information criteria (AIC) 2083, or from onset HR 2.26, 95% 1.73 -2.96, p<0.001, Cindex 0.62, AIC 2060 Figure 5A, B), as previously reported [28][29][30] . The performance of miR-181 in predicting risk of death is comparable with that of NfL (from enrollment HR 2.03, 95% CI: 1.45 -2.85, p<0.001, C-index 0.56, AIC 2096, or from onset HR 2.07, 95% CI: 1.6 -2.7, p<0.001, Cindex 0.56, AIC 2081, Figure 5A, B).…”
Section: Mir-181 and Nfl Establish A Cooperative Mirna-protein Biomarker In Prediction Of Als Prognosissupporting
confidence: 84%
“…In this study, the NFL level was detected using ultrasensitive Simoa technology in the serum, and this study showed elevated serum NFL levels in patients with ALS in China, which is consistent with the results of previous studies in Western countries. This result further proves the potential diagnostic value of serum NFL for the Chinese ALS population (11,14,18,(25)(26)(27). However, to evaluate the diagnostic performance and further establish a more accurate cut-off value of the serum NFL level for the diagnosis of ALS, the serum levels of NFL need to be investigated in a larger number of Chinese ALS patients and disease controls, including patients with other neurodegenerative diseases and non-neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 77%